Age-constrained therapsid tracks from a mid-latitude upland (Permian–Triassic transition, Los Menucos Complex, Argentina) - Citton, Paolo (2021)
Fil: Citton, Paolo. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.